OPTIMASI TEKNIK PEMURNIAN GLUKOMANAN PADA TEPUNG PORANG (Amorphophallus muelleri Blume) - Gunawan Pasaribu; Novitri Hastuti; Lisna Efiyanti; Totok K. Waluyo; Gustan Pari (BRIN Publishing, 2019)
Porang (Amorphophallus muelleri Blume) as a non-timber forest product (NTFP) has many advantagescompared to other food crops. In order to the cultivation aspect and excellence of the flour, it made this commodity afood sources in the future. Today, technical post-harvest processing become the current problems especially in gettingoptimum glucomannan. With increasing levels of glucomannan, it made the utilization and marketing of flour will bewider. This study aims to optimize of purification techniques of glucomannan. The research method is through soakingtechniques with ethanol (30%, 40% and 50%) and sodium bisulfite (2%, 3% and 4%). The results showed that theleaching technique ethanol made a significant effect on the increase in glucomannan levels. The immersion technique with50% ethanol and 2% sodium bisulfite can increase glucomannan from 32.65% to 83.96%. The process of soakingwith ethanol not affects the content of ferrum (Fe) and calcium (Ca) in porang flour.